(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: the measurements of chest expansion are performed to appreciate a patient’s treatment efficacy, standard status, and evolution of disease in relation to respiratory muscle function and chest wall mobility . Methods: In this study random collection of 1020 persons (530 male and 490 female) aged between 20 to 70 years old from Baghdad and Al-Najaf city, Participants have no history of orthopedic, neurological, rheumatologic or respiratory diseases , the smokers were excluded from this study. The chest expansion measured in 2 sites, the first site is the upper thoracic excursion, at the level of the fifth thoracic spinous process and the third intercostal space at the mid clavicular line. The second site is the lower thoracic excursion, the tape measure was placed at the level of the 10th thoracic spinous process and the tip of the xiphoid process by using tape measure. Results: The men group shows a significant larger chest expansion than women group in upper thorax (5±0.6cm, 4.2±0.7cm) for men and women respectively and at the chest expansion in the lower thorax (4.5±0.6cm, 3.7±0.6cm) for men and women respectively (p< 0.05). Chest expansion of men and women groups at the upper and lower thorax is highest at ages 20-29 year and declines thereafter with older ages. In women group, chest expansion was considerably correlated with BMI, which is decreased in the obese female. Conclusion: Chest expansion in the upper and lower thorax rise with age upsurges until the fortieth years of life, Men group have chest expansion larger than women group